A Novel Biallelic STING1 Gene Variant Causing SAVI in Two Siblings - Alghamdi, Malak Ali; Mulla, Jaazeel; Saheb Sharif-Askari, Narjes; Guzmán-Vega, Francisco J.; Arold, Stefan T.; Abd-Alwahed, Mervat; Alharbi, Nasser; Kashour, Tarek; Halwani, Rabih (Frontiers in Immunology, 2021)
STING-associated vasculopathy of infantile-onset (SAVI) is one of the newly identified types of interferonopathies. SAVI is caused by heterozygous gain-of-function mutations in the STING1. We herein report for the first time a homozygous variant in the STING1 gene in two siblings that resulted in constitutive activation of STING gene and the SAVI phenotype. Exome sequencing revealed a novel homozygous NM_198282.3: c.841C>T; p.(Arg281Trp) variant in exon 7 of the STING1 gene. The variant segregated in the family to be homozygous in all affected and either heterozygous or wild type in all healthy. Computational structural analysis of the mutants revealed changes in the STING protein structure/function. Elevated serum beta-interferon levels were observed in the patients compared to the control family members. Treatment with Janus kinase inhibitor (JAK-I) Ruxolitinib suppressed the inflammatory process, decreased beta-interferon levels, and stopped the progression of the disease.